The Influence of Relationship Marketing and Banking Digitalization on Customer Loyalty Through Corporate Governance at Bank Mandiri KCP Sidrap - Verawaty, Verawaty; Irwan, Devi Damayanti; Ceskakusumadewi (Jurnal Economic Resource, 2024)
This study aims to examine the effect of relationship marketing and banking digitalization on customer loyalty through corporate governance as an intervening variable at Bank Mandiri KCP Sidrap. The population in this study were Bank Mandiri KCP Sidrap customers, while the sample in this study was determined using the Slovin formula technique so that the number of samples obtained in this study was 100 samples. This research uses a survey method by distributing questionnaires to the research object. The statistical method used to test the hypothesis uses the partial least squares application. The results of the analysis show that relationship marketing has a significant and positive effect on corporate governance, banking digitalization has an insignificant positive and effect on corporate governance, relationship marketing has a significant and positive effect on customer loyalty, banking digitalization has a significant and positive effect on customer loyalty, corporate governance has an insignificant and positive effect on customer loyalty, relationship marketing has an insignificant and positive effect on customer loyalty through corporate governance as an intervening variable and banking digitalization has an insignificant and positive effect on customer loyalty through corporate governance as an intervening variable.